Food addiction and obesity - Anis, Muhammad Farzin; Mohamad Tajul Rijal, Nurul Balqis; Sobri, ⁠Syakirah Waheeda; Ghufron, Usamah Ali; Wan Mahmud Khairi, Wan Ainul Basyirah; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Alaa Eldin, Amirah Hannan; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
Food addiction has been vastly studied and associated with obesity. Therefore, this paper aims to analyze past studies concerning food addiction and its relationship with obesity. Most studies found that food addiction has significant correlation with obesity. The analysis revealed the strength of studies is through the diverse methodologies implied to gain data. However, most studies have limited generalizability and heavily rely on cross-sectional methods. The application of the literature to the current issue is discussed from clinical, educational, and policy aspects. Islamic perspective is also discussed, emphasizing moderation, self-control and spiritual acts as in prayer and fasting.